The Contours of Canadian Urban Justice, 1830-1875 - Marquis, Greg (Urban History Review / Revue d'histoire urbaine, 1987)
This article traces three broad stages in the evolution of two closely-related processes, nineteenth-century Canadian civic government and urban justice. Lower courts, originally administered by Crown-appointed paternalist justices of the peace, were transformed in the era of municipal incorporation into civic courts under mayors and aldermen elected by property holders. Eventually cities adopted permanent government-appointed stipendiary magistrates, ending the tradition of the urban lay magistracy and curtailing the judicial prerogatives of the office of mayor.Urban justice, the most important mid-nineteenth century municipal service, has been largely neglected by Canadian historians. Future studies will continue to examine the class nature of police and the courts and hopefully also explore the question of relative popularity of the local institutions of justice.